Fiber reinforced low cement content c30 pumping concrete and method of making the same

CN122940422APending Publication Date: 2026-10-20GUANGDONG GUANGWU METAL IND GRP CORP LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611424983.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本发明公开了一种纤维增强低水泥用量C30泵送混凝土及其制备方法,旨在解决现有低水泥用量钢纤维混凝土在钢纤维分散、钢纤维-浆体界面传力和泵送保坍性之间相互制约的问题

Benefits of technology

(1)本发明的双界面锚定型聚羧酸减水剂采用B-b-A两步链延伸拓扑构造,B段由甲基丙烯酸单元与聚乙二醇甲醚甲基丙烯酸酯单元共聚而成,具有羧酸盐锚定主链与聚醚空间位阻侧链的梳形结构,承担水泥颗粒的静电和空间位阻分散;A段由N-[2-(3,4-二乙酰氧基苯基)乙基]甲基丙烯酰胺单元与丙烯酸单元共聚而成,富集乙酰保护型邻苯二酚锚定基,可在拌合过程中,利用水泥浆体固有的高碱环境作为原位触发条件,使A段中的乙酸酯基逐步碱水解释放邻苯二酚基,实现与拌合、泵送时序相匹配的渐进锚定,无需外加触发剂或对钢纤维进行预制涂层处理,简化了工艺环节。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a fiber-reinforced, low-cement-content C30 pumpable concrete and its preparation method, belonging to the field of concrete materials technology. It aims to solve the problems of mutual constraints between steel fiber dispersion, steel fiber-slurry interface force transfer, and pumpability and slump retention in existing low-cement-content steel fiber concrete. The invention is made from cement, fly ash, slag powder, sand, crushed stone, water, steel fibers, and a dual-interface anchored polycarboxylate superplasticizer. The dual-interface anchored polycarboxylate superplasticizer is a B-b-A type block copolymer, where segment A is copolymerized from N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide units and acrylic acid units, and segment B is copolymerized from methacrylic acid units and polyethylene glycol methyl ether methacrylate units. The resulting concrete exhibits uniform steel fiber dispersion, strong steel fiber-slurry interface bonding, good fluidity and slump retention over time, and excellent compressive strength, flexural strength, and post-cracking toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete materials technology, specifically relating to a fiber-reinforced low-cement-content C30 pumpable concrete and its preparation method. Background Technology

[0002] Low-cement-dosage pumped concrete partially replaces silicate cement with mineral admixtures such as fly ash and slag powder, which can effectively reduce the heat of hydration and early shrinkage of cementitious materials, and reduce the consumption of cement clinker per unit volume of concrete while meeting the strength requirements of C30 structure. In order to further improve the flexural and crack resistance of this system, short-cut steel fibers are generally added to low-cement-dosage pumped concrete in engineering, and the post-cracking toughness of hardened concrete is improved through the bridging and pull-out energy dissipation effect of the fibers. However, the combination of steel fibers and low-cement-dosage pumped concrete has the following mutually restrictive problems: (1) After the cement dosage is reduced, the volume of the paste decreases, the paste coating layer around the steel fibers becomes thinner, the fiber-paste interface transition zone is loose, the hydration products are not rich enough, and the bridging and pull-out energy dissipation effect of the fibers cannot be fully utilized. (2) The mechanical interlocking and geometric steric hindrance of steel fibers will significantly increase the yield stress of the mixture, which will easily lead to fiber agglomeration, pump pressure increase and excessive slump loss over time; although increasing the amount of ordinary polycarboxylate superplasticizer can improve the initial fluidity in a short time, it will exacerbate the interference of free superplasticizer on cement hydration. (3) The surface of steel fibers is a dense passivated iron oxide layer, which is mainly physically adsorbed and mechanically interlocked with the silicate cement hydration phase, and the interfacial chemical bonding is weak.

[0003] Existing technology CN115677295B discloses a shotcrete for submarine tunnels and its preparation method. The technical solution involves first soaking and drying steel fibers in a silane coupling agent hydrolysate before adding them to the mixture, which is then used in combination with conventional cement, mineral admixtures, and polymer emulsions. This solution also belongs to the fiber precast coating route. The silane layer has limited stability in high-alkali cement paste, and the workability of the mixture is not simultaneously optimized at the cement particle dispersion level; the fiber treatment and paste dispersion remain independent.

[0004] In summary, existing technologies in the field of low-cement-content steel fiber pumped concrete lack a solution that can simultaneously achieve cement particle dispersion and steel fiber interface anchoring within the same polymer molecule without relying on precast fiber coatings. There is an urgent need to develop a novel type of concrete and its preparation method that can construct a steel fiber-slurry dual interface in situ during the mixing process, in order to synergistically solve the problems of pumpability, fiber dispersion, and interface force transfer under low-cement-content conditions. Summary of the Invention

[0005] This invention discloses a fiber-reinforced low-cement-content C30 pumpable concrete and its preparation method, aiming to solve the problem of mutual constraints between steel fiber dispersion, steel fiber-slurry interface force transmission and pumping slump retention in existing low-cement-content steel fiber concrete.

[0006] The specific technical solution is as follows: A fiber-reinforced, low-cement-content C30 pumpable concrete is made from the following raw materials in parts by weight: 190-215 parts cement, 85-110 parts grade II fly ash, 30-45 parts grade S95 granulated blast furnace slag powder, 0-20 parts limestone powder, 820-900 parts sand, 980-1060 parts crushed stone, 138-153 parts water, 20-47 parts steel fiber, 1.2-3.5 parts double-interface anchored polycarboxylate superplasticizer, and 0-0.01 parts defoamer; wherein the cement, grade II fly ash, grade S95 granulated blast furnace slag powder, and limestone powder together constitute... The total amount of cementitious material is controlled at 315-350 parts, and the water-cement ratio is controlled at 0.41-0.46. The water is the total effective water composed of added water and the water in the dual-interface anchored polycarboxylate superplasticizer, and the total effective water is used to calculate the water-cement ratio. The dual-interface anchored polycarboxylate superplasticizer is a BbA type block copolymer, which includes segment A and segment B. Segment A is copolymerized from N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide units and acrylic acid units. Segment B is copolymerized from methacrylic acid units and polyethylene glycol methyl ether methacrylate units.

[0007] Furthermore, the molar ratio of the N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide unit to the acrylic acid unit in segment A is (1-5):1, the molar ratio of the methacrylic acid unit to the polyethylene glycol methyl ether methacrylate unit in segment B is (0.8-3.0):1.0, and the ratio of the total molar amount of the structural units in segment B to the total molar amount of the structural units in segment A is (2.5-10):1.

[0008] Furthermore, the preparation method of the dual-interface anchored polycarboxylate superplasticizer includes the following steps: 1) Dissolve the methacrylic acid, the polyethylene glycol methyl ether methacrylate, 4-cyano-4-[(dodecylthiocarbonyl)thio]valeric acid and azobisisobutyronitrile in a mixed solvent of water and ethanol in a volume ratio of 2:1, adjust the pH to 4.5-5.5, deoxygenate by bubbling with nitrogen, and react at 50-60°C for 8-16 hours to obtain the B-segment macrochain transfer agent reaction solution; 2) Under nitrogen protection, N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide and acrylic acid were dissolved in ethanol to form a monomer mother liquor of segment A. The monomer mother liquor of segment A was added in batches to the reaction solution of macrochain transfer agent of segment B. Azobisisobutyronitrile was added, and the molar ratio of the added azobisisobutyronitrile to the total molar amount of the monomer of segment A was (0.001~0.003):1. The reaction was carried out at 50~60℃ for 8~16 hours under light-protected and nitrogen-protected conditions. After the reaction was completed, the temperature was lowered to 5~10℃, and a 30wt% hydrogen peroxide aqueous solution was added dropwise. After the dropwise addition was completed, the mixture was stirred at 20~30℃ for 2~4 hours. Then, the ethanol was removed by vacuum distillation, the pH was adjusted to 4.5~6.0, and the mixture was diluted with water to a solid content of 30~40wt%. The mixture was then sealed in a light-protected and low-oxygen headspace environment to obtain the dual-interface anchored polycarboxylate superplasticizer.

[0009] Furthermore, the amount of 4-cyano-4-[(dodecylthiocarbonyl)thio]valerate added is 0.4 to 1.2 mol% of the total molar amount of methacrylic acid and polyethylene glycol methyl ether methacrylate; the amount of azobisisobutyronitrile added is 0.15 to 0.30 times the molar amount of 4-cyano-4-[(dodecylthiocarbonyl)thio]valerate added; and the molar amount of hydrogen peroxide is 3 to 5 times the initial molar amount of 4-cyano-4-[(dodecylthiocarbonyl)thio]valerate added.

[0010] Further, the preparation method of N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide includes the following steps: dissolving 3,4-dihydroxyphenylethylamine hydrochloride in a mixed solvent of tetrahydrofuran and water, and adjusting the pH to 7.5-8.5 with sodium bicarbonate; lowering the system temperature to 0-5°C, and adding 1.05-1.15 molar equivalents of methacryloyl chloride dropwise, controlling the temperature not to exceed 5°C; continuing to stir the reaction for 2-4 hours after the addition is complete; after the reaction is completed, the reaction solution is extracted with ethyl acetate, washed with saturated brine, dried with anhydrous sodium sulfate, concentrated under reduced pressure, and purified by silica gel column chromatography to obtain N-[2-(3,4-dihydroxyphenyl)ethyl]methacrylamide. [2-(3,4-dihydroxyphenyl)ethyl]methacrylamide; 1.00 mol equivalent of the N-[2-(3,4-dihydroxyphenyl)ethyl]methacrylamide was dissolved in dichloromethane, and 2.20 mol equivalents of acetic anhydride, 2.30 mol equivalents of triethylamine, and 0.075 mol equivalents of 4-dimethylaminopyridine were added; the reaction was carried out under nitrogen protection and in the dark at 20–30 °C for 8–16 hours; after the reaction was completed, the reaction solution was washed with saturated sodium bicarbonate solution, dilute hydrochloric acid, saturated brine, dried over anhydrous sodium sulfate, concentrated under reduced pressure, and purified by silica gel column chromatography to obtain the N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide.

[0011] Furthermore, the cement is P·O 42.5 silicate cement or P·II 42.5 silicate cement; the sand is Class II natural river sand with a fineness modulus of 2.4 to 3.0; the crushed stone is continuously graded granite crushed stone with a particle size of 5 to 25 mm; the steel fiber is end-hooked cold-drawn steel fiber or corrugated cold-drawn steel fiber, the length of the steel fiber is 25 to 40 mm, the diameter is 0.45 to 0.75 mm, and the tensile strength is not less than 1000 MPa; the defoamer is a polyether-modified organosilicon defoamer.

[0012] Furthermore, the method for preparing fiber-reinforced low-cement-content C30 pumpable concrete includes the following steps: S1: Measure each raw material by weight, and put the sand, the crushed stone, the cement, the Class II fly ash, the S95 grade granulated blast furnace slag powder and the limestone powder into a forced mixer for dry mixing to obtain an aggregate-cementing material premixed system; S2: Add some of the water to the aggregate-cementing material premixing system for wet mixing to form an alkaline slurry coating layer; S3: Mix the dual-interface anchored polycarboxylate superplasticizer with the remaining water to obtain polymer mixing water, and then add the polymer mixing water and the steel fiber sequentially or adjacently into the forced mixer. S4: Continue stirring until the total wet mixing time is 160-200 seconds, add the defoamer, continue stirring for 30 seconds, and then discharge to obtain the fiber-reinforced low-cement-content C30 pumpable concrete.

[0013] Furthermore, the dry mixing time in step S1 is 20 to 40 seconds.

[0014] Furthermore, the water added in step S2 is 60% to 75% of the total water content in the raw materials, and the wet mixing time is 30 to 60 seconds.

[0015] Furthermore, in step S3, the time difference between the addition of the polymer mixing water and the steel fiber does not exceed 30 seconds, and the steel fiber is added uniformly in three batches within 60 seconds.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The dual-interface anchored polycarboxylate superplasticizer of the present invention adopts a BbA two-step chain extension topology. The B segment is copolymerized from methacrylic acid unit and polyethylene glycol methyl ether methacrylate unit, and has a comb-shaped structure with carboxylate anchored main chain and polyether steric hindrance side chain, which undertakes the electrostatic and steric hindrance dispersion of cement particles. The A segment is copolymerized from N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide unit and acrylic acid unit, which is enriched with acetyl-protected catechol anchoring groups. During the mixing process, the inherent high alkalinity environment of cement paste can be used as an in-situ triggering condition to gradually release catechol groups by alkaline hydrolysis of the acetate group in the A segment, so as to achieve progressive anchoring that matches the mixing and pumping sequence. No external triggering agent or pre-coating treatment of steel fibers is required, which simplifies the process.

[0017] (2) This invention improves the uniformity of steel fiber dispersion in the slurry, the force transfer efficiency of the steel fiber-slurry interface and the pumpability and slump retention of the mixture under low cement content conditions through the dual-functional partition structure within the same polymer molecule. The flexural strength, single fiber pull-out work and post-cracking toughness of hardened concrete are significantly improved, taking into account both pumpability and mechanical properties. Attached Figure Description

[0018] Figure 1 This is a synthetic route diagram of the dual-interface anchored polycarboxylate superplasticizer of the present invention; Figure 2 The infrared spectrum of the dual-interface anchored polycarboxylate superplasticizer obtained in Example 1 of this invention; Figure 3 This is a size exclusion chromatography / gel permeation chromatography comparison diagram of the B-segment macrochain transfer agent and the A-segment chain extension product obtained in Example 1 of the present invention. Detailed Implementation

[0019] This invention relates to fiber-reinforced, low-cement-content C30 pumpable concrete, which is made from the following raw materials by weight: 190-215 parts cement, 85-110 parts grade II fly ash, 30-45 parts grade S95 granulated blast furnace slag powder, 0-20 parts limestone powder, 820-900 parts sand, 980-1060 parts crushed stone, 138-153 parts water, 20-47 parts steel fiber, 1.2-3.5 parts double-interface anchored polycarboxylate superplasticizer, and 0-0.01 parts defoamer. The cement, grade II fly ash, grade S95 granulated blast furnace slag powder, and limestone powder together constitute the cementitious material, with the total cementitious material content controlled at 315-350 parts and the water-cement ratio controlled at 0.41-0.46. The water refers to the total effective water composed of added water and the water in the double-interface anchored polycarboxylate superplasticizer, and this total effective water is used to calculate the water-cement ratio.

[0020] The cement is P·O 42.5 silicate cement or P·II 42.5 silicate cement. The sand is Class II natural river sand with a fineness modulus of 2.4–3.0; the crushed stone is granite crushed stone with a particle size of 5–25 mm and continuous gradation. The steel fibers are end-hooked or corrugated cold-drawn steel fibers with a length of 25–40 mm, a diameter of 0.45–0.75 mm, and a tensile strength of not less than 1000 MPa. The defoamer is a polyether-modified organosilicon defoamer, used to suppress the problem of high air content caused by polymer air entrainment during mixing and pumping.

[0021] The dual-interface anchored polycarboxylate superplasticizer is a BbA type block copolymer, formed by RAFT reversible addition-fragmentation chain transfer polymerization of B-segment monomers to form a B-segment macrochain transfer agent, followed by chain extension reaction of the B-segment macrochain transfer agent by A-segment monomers. The A-segment monomers include N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide (Ac2-DMA) and acrylic acid. The B-segment monomers include methacrylic acid and polyethylene glycol methyl ether methacrylate. (See attached...) Figure 1 This describes the synthetic route for a dual-interface anchored polycarboxylate superplasticizer.

[0022] Preparation of Ac2-DMA monomers (1) Using 3,4-dihydroxyphenylethylamine hydrochloride as a raw material, it is first reacted with methacryloyl chloride under low temperature, light-proof, and nitrogen protection conditions to selectively acylate the amine group. The specific steps are as follows: 3,4-dihydroxyphenylethylamine hydrochloride is dissolved in a mixed solvent of tetrahydrofuran and water with a volume ratio of 3:1, and sodium bicarbonate is added to adjust the pH to 7.5-8.5; the system temperature is lowered to 0-5℃, and 1.05-1.15 molar equivalents of methacryloyl chloride are added dropwise, with the addition time controlled at 30-60 minutes, and the system temperature not exceeding 5℃ during the addition process; after the addition is completed, the reaction is continued to be stirred for 2-4 hours; a sample is taken for control, and the residual amount of free 3,4-dihydroxyphenylethylamine is detected by high performance liquid chromatography (HPLC) and is not higher than 0.50%, and the reaction is stopped; the reaction solution is extracted with ethyl acetate, washed with saturated brine, dried with anhydrous sodium sulfate, concentrated under reduced pressure, and purified by silica gel column chromatography to obtain N-[2-(3,4-dihydroxyphenyl)ethyl]methacrylamide, i.e., DMA monomer.

[0023] (2) Dissolve 1.00 molar equivalent of DMA monomer in dichloromethane, add 2.20 molar equivalents of acetic anhydride and 2.30 molar equivalents of triethylamine, and add 0.075 molar equivalents of 4-dimethylaminopyridine as a catalyst. React at 20-30°C for 8-16 hours under nitrogen protection and light protection. Take a sample for control. If the residual amount of DMA monomer is not higher than 0.50% by HPLC, stop the reaction. Wash the reaction solution with saturated sodium bicarbonate solution, dilute hydrochloric acid, saturated brine, and dry with anhydrous sodium sulfate. After concentration under reduced pressure, purify by silica gel column chromatography to obtain N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide, i.e., Ac2-DMA monomer.

[0024] Preparation of dual-interface anchored polycarboxylate superplasticizer (1) Preparation of B-segment macrochain transfer agent: methacrylic acid and polyethylene glycol methyl ether methacrylate were used as comonomers, with a molar ratio of (0.8-3.0):1.0. 4-cyano-4-[(dodecylthiocarbonyl)thio]valerate was used as the RAFT chain transfer agent, with an amount of 0.4-1.2 mol% of the total molar amount of the comonomers; azobisisobutyronitrile was used as the initiator, with an amount of 0.15-0.30 times the molar amount of the RAFT chain transfer agent. The monomers, chain transfer agents, and initiators were dissolved in a mixed solvent of water and ethanol at a volume ratio of 2:1 to prepare a reaction solution with a solid content of 20–40 wt%. The pH was adjusted to 4.5–5.5, and nitrogen was bubbled to remove oxygen for 30–45 minutes. The reaction was then carried out at 50–60 °C for 8–16 hours. Samples were taken for control, and the residual methacrylic acid monomer content was determined by HPLC. Fourier transform infrared spectroscopy was used to detect the changes in the characteristic absorption peaks of carbon-carbon double bonds in polyethylene glycol methyl ether methacrylate. The total monomer conversion rate was calculated to be no less than 98%. The reaction was stopped, and the system was cooled to room temperature to obtain the B-segment macrochain transfer agent reaction solution.

[0025] (2) Preparation of BbA block polymer: Under nitrogen protection, Ac2-DMA monomer and acrylic acid were pre-dissolved in ethanol at a molar ratio of (1-5):1 to form a monomer mother liquor for segment A; the monomer mother liquor for segment A was added in batches to the reaction solution of macrochain transfer agent for segment B, and the molar ratio of total monomer in segment B to total monomer in segment A was controlled to be (2.5-10):1; at the same time, initiator was added so that the molar ratio of newly added initiator to total molar amount of monomer in segment A was (0.001-0.003):1; the pH of the reaction system was maintained at 4.5-5.5, and the reaction was continued at 50-60℃ for 8-16 hours under light-proof and nitrogen protection conditions; samples were taken for control, and the residual Ac2-DMA monomer content in the reaction solution was reduced to 0.3% of the initial level by HPLC determination. Stop the reaction and immediately cool to 5–10°C. Slowly add a 30 wt% hydrogen peroxide aqueous solution to the reaction solution, with the molar amount of hydrogen peroxide being 3–5 times the initial molar amount of the RAFT chain transfer agent. Control the addition time to 30–60 minutes, and maintain the system temperature no higher than 15°C during the addition process. After the addition is complete, continue stirring the reaction at 20–30°C for 2–4 hours to oxidize and remove the trithioester groups at the polymer ends. After the reaction is complete, remove ethanol by vacuum distillation at 40–50°C and a vacuum degree of no less than 0.09 MPa until the distillate no longer increases significantly. Then adjust the pH to 4.5–6.0, dilute with water to adjust the solid content to 30–40 wt%, and encapsulate in a light-protected, low-oxygen headspace environment to obtain a BbA block polymer aqueous solution, i.e., a dual-interface anchored polycarboxylate superplasticizer.

[0026] Concrete preparation process Weigh out the cement, fly ash, slag powder, limestone powder, sand, crushed stone, water, steel fiber, double-interface anchored polycarboxylate superplasticizer, and defoamer according to the aforementioned weight proportions, and prepare the fiber-reinforced low-cement-content C30 pumpable concrete of this invention according to the following steps: S1: Add sand, crushed stone, cement, Class II fly ash, S95 grade granulated blast furnace slag powder and limestone powder into a forced mixer and dry mix for 20-40 seconds to form a homogeneous aggregate-cementing material premix system. S2: Add 60% to 75% of the total water content of the formula to the premixed system, wet mix for 30 to 60 seconds to form a uniform alkaline slurry coating layer with a pH value of not less than 12.5; S3: The dual-interface anchored polycarboxylate superplasticizer is premixed with the remaining mixing water to obtain polymer mixing water; the polymer mixing water and the steel fibers are added to the mixer sequentially or adjacently, with a time difference of no more than 30 seconds between the two additions; the steel fibers are added evenly in three batches within 60 seconds to avoid clumping; S4: Continue stirring for 160-200 seconds, add the defoamer and continue stirring for 30 seconds before discharging to obtain the fiber-reinforced low-cement-content C30 pumpable concrete.

[0027] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0028] The preferred embodiments of the present invention are described in detail below; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

[0029] Example 1 Preparation of Ac2-DMA monomer: 75.8 g (0.40 mol) of 3,4-dihydroxyphenylethylamine hydrochloride was dissolved in 600 mL of a tetrahydrofuran / water mixture (3:1 v / v). Sodium bicarbonate was added to adjust the pH to 8.0, and the mixture was kept in an ice bath at 0–5 °C. 44.8 g (equivalent to 0.42 mol based on the active content) of methacryloyl chloride was slowly added dropwise over 45 minutes, with the system temperature not exceeding 5 °C during the addition. After the addition was complete, the reaction was stirred for another 3 hours. The residual amount of free 3,4-dihydroxyphenylethylamine was detected by HPLC at 0.38%, indicating the reaction was complete. The reaction solution was extracted three times with 400 mL of ethyl acetate. The organic phases were combined, washed with saturated brine, dried over anhydrous sodium sulfate, concentrated under reduced pressure, and purified by silica gel column chromatography to obtain the DMA monomer with an HPLC purity of 99.2%. 73.6 g (0.33 mol) of the above-mentioned DMA monomer was dissolved in 600 mL of dichloromethane. 73.5 g (0.72 mol) of acetic anhydride, 76.8 g (0.76 mol) of triethylamine, and 3.06 g (0.025 mol) of 4-dimethylaminopyridine were added. The mixture was reacted at 25 °C for 12 hours under nitrogen protection and in the dark. The residual starting material was 0.12% as determined by HPLC. After the reaction, the mixture was washed successively with saturated sodium bicarbonate solution, dilute hydrochloric acid, and saturated brine. It was dried over anhydrous sodium sulfate, concentrated under reduced pressure, and purified by silica gel column chromatography to obtain Ac2-DMA monomer with an HPLC purity of 99.5%.

[0030] Preparation of BbA-type block polymer: 172 g (2.00 mol) of methacrylic acid, 1000 g (1.00 mol) of polyethylene glycol methyl ether methacrylate (side chain number average molecular weight 1000 g / mol), 12.1 g (0.03 mol) of 4-cyano-4-[(dodecylthiocarbonyl)thio]valeric acid, and 0.98 g (0.006 mol) of azobisisobutyronitrile were dissolved in 3 L of a mixed solvent of water / ethanol (volume ratio 2:1). The pH was adjusted to 5.0, and after nitrogen bubbling for deoxygenation for 30 minutes, the reaction was carried out at 55 °C for 12 hours. The residual methacrylic acid monomer content was determined by HPLC, and the change of the characteristic absorption peak of the double bond of polyethylene glycol methyl ether methacrylate was detected by Fourier transform infrared spectroscopy. The total conversion rate of B-segment monomers was calculated to be 98.5%. The reaction was stopped, and the system was cooled to room temperature to obtain the B-segment macrochain transfer agent reaction solution. 91.6 g (0.30 mol) of Ac2-DMA monomer and 7.2 g (0.10 mol) of acrylic acid were dissolved in 0.3 L of ethanol to form the monomer stock solution of segment A. This stock solution was added in three batches to the reaction solution of the macrochain transfer agent of segment B, with each batch spaced 30 minutes apart, maintaining the pH of the system at 4.5–5.5. 0.1 g (6 × 10⁻⁶) of azobisisobutyronitrile was then added as a supplement. -4 The reaction was continued at 55℃ for 12 hours under nitrogen protection and light-proof conditions. Samples were taken for control, and HPLC analysis showed that the residual Ac2-DMA monomer content in the reaction solution decreased to 0.23% of the initial level. Immediately after the reaction, the temperature was lowered to 8℃, and 13.6 g of a 30 wt% hydrogen peroxide aqueous solution was slowly added dropwise over 50 minutes, maintaining the system temperature no higher than 15℃ during the addition. After the addition was complete, the reaction was continued at 25℃ with stirring for 3 hours. Ethanol was then removed by vacuum distillation at 45℃ and a vacuum of 0.09 MPa. The pH was adjusted to 5.2, and water was added to dilute the solid content to 35 wt%. The mixture was then sealed in a light-proof, low-oxygen headspace environment to obtain a dual-interface anchored polycarboxylate superplasticizer.

[0031] Concrete preparation: Weigh out 20 kg of P·O 42.5 cement, 10.0 kg of Grade II fly ash, 3.5 kg of S95 slag powder, 1.0 kg of limestone powder, 86 kg of sand, 102.0 kg of continuously graded granite crushed stone with a particle size of 5-25 mm, 14.5 kg of water, 3.5 kg of end-hooked steel fiber (32 mm in length, 0.55 mm in diameter, tensile strength 1150 MPa), 0.24 kg of the above-mentioned double-interface anchored polycarboxylate superplasticizer (0.084 kg in solid form), and 0.0007 kg of polyether modified silicone defoamer. The total amount of cementitious materials is 34.5 kg, and the water-cement ratio is 0.42. Sand, crushed stone, cement, fly ash, slag powder, and limestone powder are added to a forced mixer and dry-mixed for 30 seconds; 8.7 kg of water is added and wet-mixed for 45 seconds, at which point the pH of the slurry is measured to be 12.8; the remaining water is premixed with a double-interface anchored polycarboxylate superplasticizer to form polymer mixing water, which is then added to the end-hook steel fibers in succession within a 15-second time difference, with the steel fibers added uniformly in three batches over 60 seconds; mixing continues until the total wet mixing time reaches 180 seconds, defoamer is added, and mixing continues for 30 seconds before discharge, yielding the fiber-reinforced low-cement-content C30 pumpable concrete of this invention.

[0032] Example 2 The preparation of the dual-interface anchored polycarboxylate superplasticizer was the same as in Example 1, except that: the amount of Ac2-DMA monomer was adjusted from 91.6 g (0.30 mol) to 68.7 g (0.225 mol), and the amount of acrylic acid was adjusted from 7.2 g (0.10 mol) to 5.4 g (0.075 mol). The molar ratio of Ac2-DMA to acrylic acid was maintained at 3:1. The total molar amount of monomers in section A was 0.30 mol, and the ratio of the total molar amount of monomers in section B (3.00 mol) to the total molar amount of monomers in section A was 10:1. The amount of azobisisobutyronitrile (AIBN) added was adjusted to 0.10 g (6 × 10⁻⁶) according to the new initiator / segment A monomer molar ratio of 0.002:1. -4 (mol). The concrete preparation process is the same as in Example 1.

[0033] Example 3 The preparation of the dual-interface anchored polycarboxylate superplasticizer was the same as in Example 1, except that: the amount of Ac2-DMA monomer was adjusted from 91.6 g (0.30 mol) to 274.9 g (0.90 mol), and the amount of acrylic acid was adjusted from 7.2 g (0.10 mol) to 21.6 g (0.30 mol). The molar ratio of Ac2-DMA to acrylic acid was maintained at 3:1. The total molar amount of monomers in section A was 1.20 mol, and the ratio of the total molar amount of monomers in section B (3.00 mol) to the total molar amount of monomers in section A was 2.5:1. The amount of azobisisobutyronitrile added was adjusted to 0.39 g (2.4 × 10⁻⁶) according to the new initiator / segment A monomer molar ratio of 0.002:1. -3 (mol). The concrete preparation process is the same as in Example 1.

[0034] Example 4 The preparation of the dual-interface anchored polycarboxylate superplasticizer is the same as in Example 1, except that: in the preparation stage of the macrochain transfer agent in segment B, the amount of methacrylic acid was adjusted from 172g (2.00mol) to 258g (3.00mol), and the molar ratio of methacrylic acid to polyethylene glycol methyl ether methacrylate was 3.0:1.0; the amount of 4-cyano-4-[(dodecyl thiocarbonyl)thio]valerate was adjusted to 19.4g (0.048mol) according to the proportion of 1.2mol% of the total molar amount of comonomers; and the amount of azobisisobutyronitrile was adjusted to 2.3g (0.014mol) according to 0.30 times the molar amount of RAFT agent. In the subsequent chain extension reaction, the total amount of monomers in stage A was adjusted synchronously according to the B / A monomer molar ratio of 7.5:1. The amount of Ac2-DMA monomer was adjusted from 91.6g (0.30mol) to 122.1g (0.40mol), and the amount of acrylic acid was adjusted from 7.2g (0.10mol) to 9.6g (0.133mol). The amount of azobisisobutyronitrile added was simultaneously adjusted to 0.13g (8×10⁻⁶). -4 (mol). The concrete preparation process is the same as in Example 1.

[0035] Example 5 The preparation of the dual-interface anchored polycarboxylate superplasticizer is the same as in Example 1, except that: in the preparation stage of the macrochain transfer agent in segment B, the amount of methacrylic acid was adjusted from 172g (2.00mol) to 68.8g (0.80mol), and the molar ratio of methacrylic acid to polyethylene glycol methyl ether methacrylate was 0.8:1.0; the amount of 4-cyano-4-[(dodecyl thiocarbonyl)thio]valerate was adjusted to 2.8g (0.007mol) according to the proportion of 0.4mol% of the total molar amount of comonomer; and the amount of azobisisobutyronitrile was adjusted to 0.2g (0.001mol) according to 0.15 times the molar amount of RAFT agent. In the subsequent chain extension reaction, the total amount of monomers in stage A was adjusted synchronously according to the B / A monomer molar ratio of 7.5:1. The amount of Ac2-DMA monomer was adjusted from 91.6g (0.30mol) to 54.9g (0.18mol), and the amount of acrylic acid was adjusted from 7.2g (0.10mol) to 4.3g (0.06mol). The amount of azobisisobutyronitrile added was simultaneously adjusted to 0.08g (4.8×10⁻⁶). -4 (mol). The concrete preparation process is the same as in Example 1.

[0036] Example 6 The preparation of the dual-interface anchored polycarboxylate superplasticizer is the same as in Example 1, except that: the amount of Ac2-DMA monomer in the chain extension stage is adjusted from 91.6 g (0.30 mol) to 101.8 g (0.333 mol), the amount of acrylic acid is adjusted from 7.2 g (0.10 mol) to 4.8 g (0.067 mol), the molar ratio of Ac2-DMA to acrylic acid is adjusted from 3:1 to 5:1, the total molar amount of monomer in segment A remains 0.40 mol, and the molar ratio of monomer B / A remains unchanged at 7.5:1. The concrete preparation process is the same as in Example 1.

[0037] Example 7 The preparation of the dual-interface anchored polycarboxylate superplasticizer is the same as in Example 1, except that: the amount of Ac2-DMA monomer in the chain extension stage is adjusted from 91.6 g (0.30 mol) to 61.1 g (0.20 mol), the amount of acrylic acid is adjusted from 7.2 g (0.10 mol) to 14.4 g (0.20 mol), the molar ratio of Ac2-DMA to acrylic acid is adjusted from 3:1 to 1:1, the total molar amount of monomer in segment A remains 0.40 mol, and the molar ratio of B / A monomers remains unchanged at 7.5:1. The concrete preparation process is the same as in Example 1.

[0038] Example 8 The concrete preparation process is the same as in Example 1, except that the amounts of each component in the concrete formula are adjusted as follows: 19.0 kg of P·O42.5 cement, 8.5 kg of Grade II fly ash, 3.0 kg of S95 slag powder, 1.0 kg of limestone powder, 82.0 kg of sand, 98.0 kg of continuously graded granite crushed stone with a particle size of 5-25 mm, 14.5 kg of water, 2.0 kg of end-hook steel fiber (same specifications as in Example 1), 0.12 kg of double-interface anchored polycarboxylate superplasticizer (0.042 kg after conversion, same as in Example 1), and 0.0005 kg of polyether modified silicone defoamer. The total amount of cementitious materials is 31.5 kg, and the water-cement ratio is 0.46. Initially, add 60% of the total water volume of the formula and wet mix for 45 seconds; premix the remaining water with the water-reducing agent to form polymer mixing water, and add it to the steel fiber successively within a 15-second time difference, and add the steel fiber evenly in 3 batches within 60 seconds; keep the total wet mixing time at 160 seconds.

[0039] Example 9 The concrete preparation process is the same as in Example 1, except that the amounts of each component in the concrete formula are adjusted as follows: 21.5 kg of P·II42.5 cement, 10.5 kg of Grade II fly ash, 3.0 kg of S95 slag powder, 90.0 kg of sand, 106.0 kg of continuously graded granite crushed stone with a particle size of 5-25 mm, 14.4 kg of water, 4.7 kg of end-hook type steel fiber (specifications same as in Example 1), 0.35 kg of the above-mentioned double-interface anchored polycarboxylate superplasticizer (0.122 kg in solid form, same as in Example 1), and 0.0010 kg of polyether modified silicone defoamer. The total amount of cementitious materials is 35.0 kg, and the water-cement ratio is 0.41. Initially, 75% of the total water volume of the formula is added and wet-mixed for 45 seconds; the remaining water is premixed with the superplasticizer to form polymer mixing water, and then added to the mixture with the steel fiber within a 15-second time difference. The steel fiber is added evenly in three batches within 60 seconds; the total wet mixing time is maintained at 200 seconds.

[0040] Comparative Example 1 Instead of using a dual-interface anchored polycarboxylate superplasticizer, a commercially available comb-shaped polycarboxylate superplasticizer of equal solids mass (28% water reduction, main chain of methacrylic acid, side chain of polyethylene glycol methyl ether methacrylate, no Ac2-DMA structural units, non-block structure) was used, with a polymer solids content of 0.25% of the cementitious material mass. The steel fibers used were untreated, end-hooked steel fibers with the same specifications as in Example 1. The remaining raw material proportions and concrete preparation process were the same as in Example 1.

[0041] Comparative Example 2 The synthesis of the two-step chain-extended BbA polymer was changed to a one-step random copolymerization. The following components were used: 172 g (2.00 mol) of methacrylic acid, 1000 g (1.00 mol) of polyethylene glycol methyl ether methacrylate (side chain number average molecular weight 1000 g / mol), 91.6 g (0.30 mol) of Ac2-DMA monomer, 7.2 g (0.10 mol) of acrylic acid, 12.1 g (0.03 mol) of 4-cyano-4-[(dodecylthiocarbonyl)thio]valerate, and 1.08 g (6.6 × 10⁻⁶) of azobisisobutyronitrile (AIBN). -3 The mol) was dissolved in 3 L of a water / ethanol mixture (2:1 volume ratio), the pH was adjusted to 5.0, and the mixture was deoxygenated by nitrogen bubbling for 30 minutes before reacting at 55 °C for 24 hours. After the reaction was completed, the residual Ac2-DMA monomer content in the reaction solution was determined by HPLC to be 0.30%. Due to the lack of BbA block topology in the one-step copolymerization, the Ac2-DMA units were randomly distributed along the main chain. The proportions of other raw materials and the concrete preparation process were the same as in Example 1.

[0042] Comparative Example 3 The acetic anhydride acylation step in the preparation of Ac2-DMA monomers was skipped, and N-[2-(3,4-dihydroxyphenyl)ethyl]methacrylamide, i.e., the unprotected DMA monomer, was directly used as the A-segment functional monomer in the chain extension reaction; the molar number of reactants and the reaction conditions were the same as in the chain extension stage of Example 1. The proportions of other raw materials for concrete and the concrete preparation process were the same as in Example 1.

[0043] Comparative Example 4 Instead of using a dual-interface anchored polycarboxylate superplasticizer, a commercially available comb-shaped polycarboxylate superplasticizer of equal solid mass (specifications same as Comparative Example 1) was used. The hooked steel fibers were pre-modified in an aqueous solution of 3,4-dihydroxyphenylethylamine. The preparation steps for the 3,4-dihydroxyphenylethylamine pre-coated steel fibers were as follows: the hooked steel fibers (specifications same as in Example 1) were immersed in an aqueous solution containing 2 g / L of 3,4-dihydroxyphenylethylamine hydrochloride and a tris(hydroxymethyl)aminomethane buffer at pH 8.5. The solution was stirred and soaked for 24 hours at room temperature under aerobic conditions. After removal, the fibers were washed three times with deionized water and dried at 60°C for 6 hours to obtain pre-treated steel fibers with a polymerized 3,4-dihydroxyphenylethylamine coating. The amount of steel fiber used was the same as in Example 1. The proportions of other concrete raw materials and the concrete preparation process were the same as in Example 1.

[0044] Performance testing: 1. Workability test of the mixture Refer to GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures".

[0045] Sample preparation: Immediately after the fiber-reinforced low-cement C30 pumped concrete obtained from each embodiment and comparative example is discharged, take about 50L of the mixture and remove the aggregate with a maximum particle size greater than 25mm.

[0046] Test procedure: Slump was measured at 0 minutes and 60 minutes after discharge using a standard slump cone and slump spread test; air content of fresh concrete was measured using a direct-reading air content meter. The ambient temperature was 20±3℃, and the relative humidity was not less than 50%. Each test was performed three times, and the average value was recorded. Initial slump, 60-minute slump, and air content were recorded.

[0047] 2. Compressive strength test Refer to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete".

[0048] Sample preparation: After the fiber-reinforced low-cement C30 pumped concrete obtained from each embodiment and comparative example was discharged, 100mm×100mm×100mm cube molds were poured. After mechanical vibration molding, the molds were covered with film and left to stand for 24 hours before demolding. The molds were then cured in a standard curing room at a temperature of 20±2℃ and a relative humidity of not less than 95% for 3 days, 7 days, and 28 days.

[0049] Testing procedure: The specimen is mounted on a compression testing machine and continuously and uniformly loaded at a loading rate of 0.5–0.8 MPa / s until the specimen fails. The maximum failure load is recorded, and the compressive strength is calculated according to the formula. Six specimens are tested in each group, and the average value is taken. Abnormal data with a deviation exceeding 15% of the average value are discarded.

[0050] 3. Flexural strength test Refer to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete".

[0051] Sample preparation: 100mm×100mm×400mm prism specimens were prepared from fiber-reinforced low-cement C30 pumped concrete obtained from each embodiment and comparative example. After mechanical vibration molding, the specimens were covered with a film and left to stand for 24 hours before demolding. The specimens were then cured in a standard curing room at a temperature of 20±2℃ and a relative humidity of not less than 95% for 28 days.

[0052] Test procedure: A three-point loading method was used, with a loading rate of 0.05–0.08 MPa / s, continuously and uniformly loaded until the specimen fractured. The maximum failure load was recorded, and the flexural strength was calculated using the formula. Six specimens were tested in each group, and the average value was taken.

[0053] 4. Single fiber pull-out test Refer to JG / T 472-2015 "Steel Fiber Reinforced Concrete".

[0054] Sample preparation: 50mm×50mm×50mm dog bone-shaped specimens were prepared from fiber-reinforced low-cement C30 pumped concrete obtained from each embodiment and comparative example. During specimen molding, a single hook-shaped steel fiber was positioned and embedded along the central axis of the mold to a depth of 15mm, with 10mm of the fiber protruding end reserved for clamping. After molding, the specimens were covered with a film and left to stand for 24 hours before demolding. They were then cured in a standard curing room at a temperature of 20±2℃ and a relative humidity of not less than 95% for 28 days.

[0055] Test Procedure: The specimen is clamped on a universal testing machine and stretched uniformly along the fiber axis at a rate of 0.5 mm / min until the fiber is completely pulled out; the load-displacement curve is recorded throughout the process. The pull-out work of a single fiber is calculated by integrating the area under the curve to a displacement of 15 mm. Nine specimens are tested in each group, and the average value is taken. Abnormal data due to fiber breakage rather than pull-out are discarded.

[0056] Fourier transform infrared spectroscopy structural characterization (1) Detection process: The molecular structure of the dual-interface anchored polycarboxylate superplasticizer obtained in Example 1 was characterized and analyzed using Fourier transform infrared spectroscopy. The sampling method was the potassium bromide coating method: approximately 50 μL of a 35 wt% aqueous solution of the dual-interface anchored polycarboxylate superplasticizer was dropped onto the surface of a potassium bromide salt sheet and vacuum-dried in a 50°C vacuum drying oven for 12 hours to obtain a uniformly coated transparent polymer film; the salt sheet carrying the sample was placed at the focal point of the infrared light path for testing. The scanning range was set to 4000 cm⁻¹. -1 Up to 500cm -1 The mid-infrared region has a spectral resolution of 4 cm⁻¹. -1 After background subtraction, a total of 32 scans were performed.

[0057] (2) Characterization results: as shown in the appendix Figure 2 As shown, 3440cm -1 The broad and strong absorption band is attributed to the stretching vibration of the OH group associated with the carboxylic acid, proving the presence of free carboxylic acid groups in the molecular chain, consisting of methacrylic acid units and acrylic acid units; 3340 cm⁻¹ -1 The moderate-intensity shoulder peak superimposed within the aforementioned broadband region belongs to the second-order amide NH stretching vibration, and is associated with 1652 cm⁻¹. -1 Amide I and 1540cm -1 The characteristic peaks of amide II together form a complete secondary amide characteristic triplet, proving that the amide linkage structure of the N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide unit in segment A is completely preserved; 1762 cm⁻¹ -1 The C=O stretching vibration attributed to aryl acetates, with a value of 1245 cm⁻¹ -1 The antisymmetric stretching vibrations of the aryl acetate corroborate each other, proving that the acetyl protecting group in the A-segment structural unit is intact and did not undergo hydrolysis during synthesis; 1725cm -1 The absorption is attributed to the overlap of the C=O stretching vibration of the ester group in the main chain of polyethylene glycol methyl ether methacrylate and the C=O stretching vibration of the carboxylic acid group in methacrylic acid and acrylic acid units, at 1105 cm⁻¹. -1 The COC antisymmetric stretching vibrations attributed to the polyether side chains demonstrate the successful copolymerization of the methacrylic acid unit and the polyethylene glycol methyl ether methacrylate unit in segment B, as well as the integrity of the polyether side chains; 1636 cm⁻¹ -1 No obvious C=C stretching vibration characteristic peaks were detected, proving that the C=C double bonds in both the B and A segments of the monomers had fully reacted during the RAFT two-step polymerization. These infrared spectral characteristics collectively confirm the complete coexistence of the two key functional structural units: the dispersed segment in segment B and the acetyl-protected catechol anchoring segment in segment A, indicating the successful construction of the BbA two-step chain extension topology.

[0058] Size exclusion chromatography / gel permeation chromatography (SEC / GPC) characterization (1) Detection process: Gel permeation chromatography was used to characterize the molecular weight, molecular weight distribution, and chain extension behavior of the B-segment macrochain transfer agent obtained during the preparation process of Example 1 and the chain extension product obtained after the A-segment chain extension and before hydrogen peroxide treatment. The reaction solution of the B-segment macrochain transfer agent obtained after the B-segment polymerization and the reaction solution of the chain extension product obtained 12 hours after the A-segment chain extension were taken, diluted, filtered, and then tested. An aqueous SEC / GPC system and a differential refractive index detector were used. The mobile phase was an aqueous solution composed of 0.10 mol / L sodium nitrate and 10 mmol / L phosphate buffer, with a pH of 7.0 ± 0.1, a flow rate of 0.60 mL / min, and a column temperature and detector temperature of 35℃. A series of narrow-distribution polyethylene glycol / polyoxyethylene standards were used for molecular weight calibration. Based on the SEC / GPC elution curve of the sample and the calibration curve, the relative number-average molecular weight Mn, relative weight-average molecular weight Mw, and dispersion coefficient of the sample were calculated by the chromatographic data processing software. ,in =Mw / Mn. The B-segment macrochain transfer agent and the chain extension product were tested under the same conditions to compare the changes in the main peak retention time and molecular weight distribution before and after chain extension.

[0059] (2) Characterization results: as shown in the appendix Figure 3 As shown, the SEC / GPC retention time of the B-segment macrochain transfer agent obtained in Example 1 was approximately 16.73 min, its number-average molecular weight Mn was 37800 g / mol, its weight-average molecular weight Mw was 46100 g / mol, and its dispersive index was [missing information]. The value was 1.22 (see Table 1). The retention time of the main peak of the chain-extended product after chain extension of segment A was approximately 16.36 min. After chain extension, the main peak shifted towards a shorter retention time direction by approximately 0.37 min. Its number-average molecular weight Mn was 41300 g / mol, its weight-average molecular weight Mw was 50800 g / mol, and its dispersion index was... The value was 1.23 (see Table 1). Compared with the B-segment macrochain transfer agent, the SEC / GPC main peak of the chain extension product shifted to a shorter retention time by approximately 0.37 min. Simultaneously, Mn increased from 37800 g / mol to 41300 g / mol, and Mw increased from 46100 g / mol to 50800 g / mol, while the dispersion coefficient... The results remained largely stable. Both samples exhibited a single main distribution peak, without any obvious independent low-molecular-weight secondary peaks or a second main peak. Furthermore, the molecular weight distribution of the chain-extending products and the B-segment macrochain transfer agent remained generally concentrated. For size exclusion chromatography, under consistent testing conditions and without significant adsorption or polyelectrolyte interference, shorter retention times correspond to larger hydrodynamic volumes. Therefore, the shift of the main peak towards shorter retention times and the simultaneous increase in Mn and Mw indicate that the polymer chain of the original B-segment macrochain transfer agent further increased after the addition of the A-segment monomer and the second-stage RAFT reaction. Combined with the stepwise RAFT polymerization process of this invention—preparing the B-segment macrochain transfer agent from methacrylic acid and polyethylene glycol methyl ether methacrylate, then adding Ac2-DMA monomer and acrylic acid for the second-stage chain extension—and the characterization results of the characteristic structural units of the A and B segments by Fourier transform infrared spectroscopy, along with the chain growth results reflected in the aforementioned SEC / GPC, all these factors support the continued chain extension of the B-segment macrochain transfer agent by the A-segment monomer, forming the aforementioned BbA-type partitioned structure.

[0060] Table 1. SEC / GPC molecular weight characterization results of the B-segment macrochain transfer agent and A-segment chain extension product obtained in Example 1.

[0061] Table 2. Workability test results of concrete mixtures in the examples and comparative examples.

[0062] Table 3. Results of concrete compressive strength tests in the examples and comparative examples.

[0063] Table 4. Results of concrete flexural strength and single fiber pull-out energy tests in the examples and comparative examples.

[0064] Results analysis: (1) As shown in Tables 2 to 4, the fiber-reinforced low-cement C30 pumped concrete obtained in Examples 1 to 9 exhibits comprehensive performance advantages in multiple indicators such as initial workability, slump retention over time, compressive strength at various ages, 28-day flexural strength, and single fiber pull-out work. Among them, the comprehensive performance of Example 1 is the most outstanding, proving that the median parameter configuration defined by the present invention achieves good synergy between the cement particle dispersion function of section B and the steel fiber interface anchoring function of section A. Examples 2 to 9 respectively adjusted the monomer molar ratio of section A and section B in the polymer synthesis process, the monomer composition of section A and section B, and the amount of each raw material in the concrete. Although the performance indicators of each example fluctuated slightly compared with Example 1, they were all within a reasonable range. The compressive strength at various ages met the design requirements of C30 pumped concrete, and the flexural strength and single fiber pull-out work were significantly higher than all comparative examples, which together verified the feasibility of the polymer structural parameter window and concrete formula composition range defined by the present invention.

[0065] (2) Comparative Example 1 uses a combination of commercially available polycarboxylate superplasticizer and untreated steel fibers. Lacking the BbA block topology, acetyl-protected base triggering mechanism, and the steel fiber-slurry dual interface formed by the in-situ reaction of the polymer described in this invention, the workability and mechanical properties significantly decreased. The slump loss over time was significantly increased, and the flexural strength and single fiber pull-out work showed the largest decreases. This reflects the inherent limitation of conventional superplasticizers, which only provide cement particle dispersion and cannot participate in the construction of the steel fiber interface. Comparative Example 2 uses a copolymer with comparable composition prepared by a one-step random copolymerization method. Although the Ac2-DMA units and acetyl-protected groups were retained, the lack of the BbA partitioned topology formed by two-step chain extension resulted in the random distribution of Ac2-DMA units along the main chain. The cement particle dispersion function of the B segment was interfered with, and the steel fiber interface anchoring could not occur orientally. All workability and mechanical properties were inferior to those of Example 1, demonstrating the necessity of the BbA two-step chain extension topology described in this invention for achieving dual interface synergy.

[0066] (3) Comparative Example 3 uses DMA monomers without acetyl protection to prepare BbA block polymers. Catechol is in a free state during storage and the initial feeding stage, and non-selective adsorption and oxidative crosslinking are aggravated. Early retardation affects the hydration process, and workability, slump retention, compressive strength at all ages, flexural strength and single fiber pull-out work all show the largest decrease. This proves the necessity of the acetyl protection described in this invention for polymer storage stability and in-situ deprotection that matches the timing of the formation of alkaline slurry after feeding. Comparative Example 4 uses a conventional water-reducing agent combined with 3,4-dihydroxyphenylethylamine to pre-coat steel fibers. Although acetyl anchoring groups are pre-introduced on the surface of steel fibers, the pre-coated coating and slurry dispersion functions are independent of each other. No synergistic steel fiber-slurry dual interface is formed within the same polymer molecule. Moreover, the pre-coated coating may be oxidized and powdered during storage, transportation and mixing. The improvement in workability and mechanical properties is limited. This verifies the advantage of the technical route of in-situ construction of dual interface during the mixing process of the polymer in this invention compared with the route of pre-coating on the fiber surface.

[0067] In summary, this invention designs a dual-interface anchored polycarboxylate superplasticizer with a BbA two-step chain extension topology. Segment A is copolymerized from N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide units and acrylic acid units, while segment B is copolymerized from methacrylic acid units and polyethylene glycol methyl ether methacrylate units. Utilizing the inherently high alkalinity of cement paste as an in-situ triggering condition, the acetyl protecting groups in segment A are gradually degraded by alkaline hydrolysis during mixing, releasing catechol anchoring groups. The resulting concrete exhibits uniform steel fiber dispersion, strong steel fiber-paste interface bonding, good fluidity and slump retention over time, and excellent compressive strength, flexural strength, and post-cracking toughness.

Claims

1. A fiber-reinforced, low-cement-content C30 pumpable concrete, characterized in that, The fiber-reinforced low-cement-content C30 pumped concrete is made from the following raw materials in parts by weight: 190-215 parts cement, 85-110 parts grade II fly ash, 30-45 parts grade S95 granulated blast furnace slag powder, 0-20 parts limestone powder, 820-900 parts sand, 980-1060 parts crushed stone, 138-153 parts water, 20-47 parts steel fiber, 1.2-3.5 parts double-interface anchored polycarboxylate superplasticizer, and 0-0.01 parts defoamer; the cement, grade II fly ash, grade S95 granulated blast furnace slag powder, and limestone powder together constitute the cementitious material, and the total cementitious material... The dosage is controlled at 315-350 parts, and the water-to-binder ratio is controlled at 0.41-0.46; the water is the total effective water composed of added water and the water in the dual-interface anchored polycarboxylate superplasticizer, and the total effective water is used to calculate the water-to-binder ratio; the dual-interface anchored polycarboxylate superplasticizer is a BbA type block copolymer, which includes segment A and segment B; segment A is copolymerized from N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide units and acrylic acid units; segment B is copolymerized from methacrylic acid units and polyethylene glycol methyl ether methacrylate units.

2. The fiber-reinforced low-cement-content C30 pumpable concrete as described in claim 1, characterized in that, The molar ratio of the N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide unit to the acrylic acid unit in segment A is (1-5):1, the molar ratio of the methacrylic acid unit to the polyethylene glycol methyl ether methacrylate unit in segment B is (0.8-3.0):1.0, and the ratio of the total molar amount of the structural units in segment B to the total molar amount of the structural units in segment A is (2.5-10):

1.

3. The fiber-reinforced low-cement-content C30 pumpable concrete as described in claim 1, characterized in that, The preparation method of the dual-interface anchored polycarboxylate superplasticizer includes the following steps: 1) Dissolve the methacrylic acid, the polyethylene glycol methyl ether methacrylate, 4-cyano-4-[(dodecylthiocarbonyl)thio]valeric acid and azobisisobutyronitrile in a mixed solvent of water and ethanol in a volume ratio of 2:1, adjust the pH to 4.5-5.5, deoxygenate by bubbling with nitrogen, and react at 50-60°C for 8-16 hours to obtain the B-segment macrochain transfer agent reaction solution; 2) Under nitrogen protection, N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide and acrylic acid were dissolved in ethanol to form a monomer mother liquor of segment A. The monomer mother liquor of segment A was added in batches to the reaction solution of macrochain transfer agent of segment B. Azobisisobutyronitrile was added, and the molar ratio of the added azobisisobutyronitrile to the total molar amount of the monomer of segment A was (0.001~0.003):

1. The reaction was carried out at 50~60℃ for 8~16 hours under light-protected and nitrogen-protected conditions. After the reaction was completed, the temperature was lowered to 5~10℃, and a 30wt% hydrogen peroxide aqueous solution was added dropwise. After the dropwise addition was completed, the mixture was stirred at 20~30℃ for 2~4 hours. Then, the ethanol was removed by vacuum distillation, the pH was adjusted to 4.5~6.0, and the mixture was diluted with water to a solid content of 30~40wt%. The mixture was then sealed in a light-protected and low-oxygen headspace environment to obtain the dual-interface anchored polycarboxylate superplasticizer.

4. The fiber-reinforced low-cement-content C30 pumpable concrete as described in claim 3, characterized in that, The amount of 4-cyano-4-[(dodecylthiocarbonyl)thio]valerate added is 0.4 to 1.2 mol% of the total molar amount of methacrylic acid and polyethylene glycol methyl ether methacrylate; the amount of azobisisobutyronitrile added is 0.15 to 0.30 times the molar amount of 4-cyano-4-[(dodecylthiocarbonyl)thio]valerate added; and the molar amount of hydrogen peroxide is 3 to 5 times the initial molar amount of 4-cyano-4-[(dodecylthiocarbonyl)thio]valerate added.

5. The fiber-reinforced low-cement-content C30 pumpable concrete as described in claim 1, characterized in that, The preparation method of N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide includes the following steps: dissolving 3,4-dihydroxyphenylethylamine hydrochloride in a mixed solvent of tetrahydrofuran and water, and adding sodium bicarbonate to adjust the pH to 7.5-8.5; lowering the system temperature to 0-5°C, and adding 1.05-1.15 molar equivalents of methacryloyl chloride dropwise, controlling the temperature not to exceed 5°C; continuing to stir the reaction for 2-4 hours after the addition is complete; after the reaction is completed, the reaction solution is extracted with ethyl acetate, washed with saturated brine, dried with anhydrous sodium sulfate, concentrated under reduced pressure, and purified by silica gel column chromatography to obtain N-[2-(3,4-dihydroxyphenyl)ethyl]methacrylamide. N-[2-(3,4-dihydroxyphenyl)ethyl]methacrylamide was prepared by dissolving 1.00 mol equivalent of the N-[2-(3,4-dihydroxyphenyl)ethyl]methacrylamide in dichloromethane, adding 2.20 mol equivalents of acetic anhydride, 2.30 mol equivalents of triethylamine, and 0.075 mol equivalents of 4-dimethylaminopyridine. The reaction was carried out under nitrogen protection and in the dark at 20–30 °C for 8–16 hours. After the reaction was completed, the reaction solution was washed with saturated sodium bicarbonate solution, dilute hydrochloric acid, saturated brine, dried over anhydrous sodium sulfate, concentrated under reduced pressure, and purified by silica gel column chromatography to obtain the N-[2-(3,4-diacetoxyphenyl)ethyl]methacrylamide.

6. The fiber-reinforced low-cement-content C30 pumpable concrete as described in claim 1, characterized in that, The cement is P·O 42.5 silicate cement or P·II 42.5 silicate cement; the sand is Class II natural river sand with a fineness modulus of 2.4 to 3.0; the crushed stone is continuously graded granite crushed stone with a particle size of 5 to 25 mm; the steel fiber is end-hook type cold-drawn steel fiber or corrugated type cold-drawn steel fiber, the length of the steel fiber is 25 to 40 mm, the diameter is 0.45 to 0.75 mm, and the tensile strength is not less than 1000 MPa; the defoamer is a polyether modified organosilicon defoamer.

7. A method for preparing fiber-reinforced low-cement-content C30 pumpable concrete according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1: Measure each raw material by weight, and put the sand, the crushed stone, the cement, the Class II fly ash, the S95 grade granulated blast furnace slag powder and the limestone powder into a forced mixer for dry mixing to obtain an aggregate-cementing material premixed system; S2: Add some of the water to the aggregate-cementing material premixing system for wet mixing to form an alkaline slurry coating layer; S3: Mix the dual-interface anchored polycarboxylate superplasticizer with the remaining water to obtain polymer mixing water, and then add the polymer mixing water and the steel fiber sequentially or adjacently into the forced mixer. S4: Continue stirring until the total wet mixing time is 160-200 seconds, add the defoamer, continue stirring for 30 seconds, and then discharge to obtain the fiber-reinforced low-cement-content C30 pumpable concrete.

8. The method for preparing fiber-reinforced low-cement-content C30 pumpable concrete as described in claim 7, characterized in that, The dry mixing time in step S1 is 20 to 40 seconds.

9. The method for preparing fiber-reinforced low-cement-content C30 pumpable concrete as described in claim 7, characterized in that, The water added in step S2 is 60% to 75% of the total water content in the raw materials, and the wet mixing time is 30 to 60 seconds.

10. The method for preparing fiber-reinforced low-cement-content C30 pumpable concrete as described in claim 7, characterized in that, In step S3, the time difference between the addition of the polymer mixing water and the steel fiber shall not exceed 30 seconds, and the steel fiber shall be added evenly in three batches within 60 seconds.

Citation Information

Patent Citations

  • A shotcrete for submarine tunnels, its preparation method, and its application.

    CN115677295B